DEVELOPING THE STUDENTS’ WRITING SKILL BY USING TECHNOLOGY BASED LEARNING MODEL AT 1ST SEMESTER OF TERANG BANGSA UNIVERSITY - Sainyakit, Paulus (Acitya: Journal of Teaching and Education, 2025)
Writing can be a tool for extending the students’ knowledge. It means that it can be the ways of writing process which are in the form of ink streaks and messages form in the use of social medias. In doing so, we can use the technology-based learning in the teaching and learning process, especially for teaching and learning writing. This research is aimed to develop the students’ writing skill by using technology-based learning model at 1st semester of Terang Bangsa University. The research design applied in this research is Action Research. The approaches of this research are mixed methods. The Instruments are Observation and Test. The results show that all of the cycles have increased on Pre-Test and Post-Test. The results of the students’ Pre-Test, they got 34% in cycle 1, 49% in cycle 2 and 67% in cycle 3. Then, the results of the students’ Post-Test, they got 38% in cycle 1, 54% in cycle 2 and 71% in cycle 3. It is also found out that the students are motivated to learn the material of writing by using Technology-based learning model. Due to the limitations, the researcher suggests that the teacher can use these results for the teaching and learning process especially the use of technology-based learning to improve writing skill, for educational Institution, this research can address learning and teaching in order to improve the teachers’ professional attitude. Then, for the further researchers, this research can be a reference to do the research